1989
DOI: 10.2214/ajr.153.2.387
|View full text |Cite
|
Sign up to set email alerts
|

Contrast enhancement in spinal MR imaging

Abstract: We evaluated 44 patients with suspected spinal tumors or previous laminectomies with gadolinium-DTPA MR imaging in order to characterize the enhancement in normal, postoperative, and neoplastic intraspinal tissue. Using the signal intensity of CSF as an internal control, we calculated the percentage increase in signal intensity from pre-to postgadolinium studies. Tumors (astrocytoma, ependymoma, schwannoma) enhanced

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 5 publications
1
20
0
Order By: Relevance
“…3 As such, most articles regarding the MR imaging findings of intramedullary astrocytomas were limited with respect to the number of patients; therefore, the frequency of nonenhancing astrocytomas varied from 0% to 50%. [7][8][9][10][11][12][13] However, the largest scale study showed that nonenhancing intramedullary astrocytomas were present in 29% of 35 patients with spinal cord tumors, 7 similar to those in the present study.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…3 As such, most articles regarding the MR imaging findings of intramedullary astrocytomas were limited with respect to the number of patients; therefore, the frequency of nonenhancing astrocytomas varied from 0% to 50%. [7][8][9][10][11][12][13] However, the largest scale study showed that nonenhancing intramedullary astrocytomas were present in 29% of 35 patients with spinal cord tumors, 7 similar to those in the present study.…”
Section: Discussionsupporting
confidence: 83%
“…[7][8][9][10][11][12][13] The full text from 6 English articles was reviewed and 1 article written in Chinese was reviewed by abstract alone. Literature review was performed by 1 author (H.S.S.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…2 5 The differentiation between the spinal nerve root sheath and scars is more reliable in Gd enhanced than in un enhanced MR images. 26 On the basis of our present experience with the application of gadolinium com pounds in spinal cord injuries, we think that in order to obtain the maximal benefit from enhancement patients should be very care fully selected. We do not apply gadolinium systemically, but prefer first to consider the use of appropriate pulse sequences and suppression techniques.…”
Section: Current Advances In Mri 307mentioning
confidence: 93%
“…Of the 169 spinal cord ependymomas included in the Mayo series, 44% were located in the filum terminale; the remainder were termed intramedullary. 9 In the cervical and thoracic cord, they were seen as cord expansion in sagittal and axial planes, whereas at the cauda equina, they appeared as bulky intradural masses.…”
Section: Discussionmentioning
confidence: 99%